Navigating the post-pandemic frontier: Exploring factors influencing technology adoption in Indonesian microenterprises - Thaha, Abdurrahman Rahim; Antoro, Aji Fajar Suryo; Salmon, Indra Pratama Putra; Purnamasari, Rita (Universitas Tarumanagara, 2024)
This study investigates the intricacies of technology adoption dynamics in the post-pandemic Indonesian microenterprise landscape. Using the Technology, Organization, Environment (TOE) framework and leveraging SmartPLS analysis on a sample of 300 microenterprises. This study reveals the impact of environmental, organizational, and technological factors and their profound influence on technology adoption decisions. The findings explain the compelling and affirmative impact of environmental factors, underscoring the critical role of regulatory support and economic conditions in driving technology adoption initiatives. Meanwhile, organizational factors show a positive albeit relatively weaker relationship, emphasizing the need for micro-enterprises to develop organizational capacity and foster a culture of innovation. Technological factors emerged as decisive, indicating that innovative solutions are an indispensable catalyst to drive technology adoption. These insights have profound implications for policymakers, microenterprise owners, and technology pioneers, offering strategic pathways to foster technology adoption, enhance resilience, and catalyze economic revival in the microenterprise sector. Studi ini menyelidiki seluk-beluk dinamika adopsi teknologi dalam lanskap usaha mikro Indonesia pasca pandemi. Menggunakan kerangka Technology, Organization, Environment (TOE) dan memanfaatkan analisis SmartPLS pada sampel 300 usaha mikro. Studi ini mengungkapkan dampak faktor lingkungan, organisasi, dan teknologi serta pengaruhnya yang besar terhadap keputusan adopsi teknologi. Temuan ini menjelaskan dampak yang menarik dan afirmatif dari faktor lingkungan, menggarisbawahi peran penting dari dukungan peraturan dan kondisi ekonomi dalam mendorong inisiatif adopsi teknologi. Sementara itu, faktor organisasi menunjukkan hubungan yang positif meskipun relatif lemah, sehingga menekankan perlunya usaha mikro untuk mengembangkan kapasitas organisasi dan menumbuhkan budaya inovasi. Faktor teknologi menjadi faktor penentu, yang menunjukkan bahwa solusi inovatif merupakan katalis yang sangat diperlukan untuk mendorong adopsi teknologi. Wawasan ini mempunyai implikasi besar bagi para pembuat kebijakan, pemilik usaha mikro, dan pionir teknologi, yang menawarkan jalur strategis untuk mendorong adopsi teknologi, meningkatkan ketahanan, dan mendorong kebangkitan ekonomi di sektor usaha mikro.